Wheelchair Movement Control System - Arfah , Ariffin (UTeM, 2009)
This project is mainly to modify wheelchair that can move without the user holding the wheel. Wheelchair movement control system is a project that develops to help handicapped person or sick people who use the wheelchair. The main concept and objective for this project is to control and move the wheelchair using switch and motors. Before this, this project is done by Mr. Zamre Abd. Ghani. His project also same, it is to move the wheelchair by using motor. This project continues and upgrades work carried out to control the wheelchair movement. This project will include additional features on LCD display showing the direction of the wheelchair movement. LCD is used to display the direction such as left, right, forward and reverse. This report is focused on the circuit design and also the operation. Switch circuit will be used to determine the direction of wheelchair and connect to PIC input circuit.